Chirp gating enhances performance of chirp spread spectrum systems - Pohl, Alfred; Reindl, Leonhard; Seifert, Franz; Weigel, Robert (IEEE 1998 MTT/AP International Workshop on Commercial Radio Sensor and Communication Techniques, 1998)
The application of chirp spread spectrum systems for a reliable indoor communication system operated in the 2.45 GHz ISM band is shown. A test system have been built applying surface acoustic wave dispersive delay lines (SAW chirp filters) for chirp impulse compression. Gating of a chirp signal and the according compressive device means gating in time and frequency domain simultaneously. If only a part of the chirp is transmitted or received, the impulse compression still delivers useful output signals. This fact can be utilized for transmission of additional data information in chirp gaps with gap position modulation and for leaving out a sub band during transmission, to avoid jamming of other narrowband communication systems operating in this frequency band. It also can be applied for our new method of adaptive interference suppression introduced here. With a tapped dispersive SAW delay line the frequency band for chirp transmission is divided into a number of intervals. If one or some of these sections are occupied, they can be spared out in the transmitter or if a narrowband jammer is received within such subbands, they can be gated and disregarded for the impulse compression. This yields a technique for fast adaptive jamming cancellation without a loss of the simplicity of a SAW based Spread Spectrum system. The experimental system was tested in different electromagnetically polluted indoor areas. Simulations and some preliminary experimental results are presented.
elib2cris::1512001600,pohl1998